An Efficient Virus-Induced Gene Silencing System for Functional Genomics Research in Walnut (Juglans regia L.) Fruits - Wang, Yifan; Huang, Ning; Ye, Niu; Qiu, Lingyu; Li, Yadong; Ma, Huiling (Frontiers in Plant Science, 2021)
The Persian walnut (Juglans regia L.) is a leading source of woody oil in warm temperate regions and has high nutritional and medicinal values. It also provides both tree nuts and woody products. Nevertheless, incomplete characterization of the walnut genetic system limits the walnut gene function analysis. This study used the tobacco rattle virus (TRV) vector to construct an infectious pTRV-JrPDS recombinant clone. A co-culture inoculation method utilizing Agrobacterium was screened out from four inoculation methods and optimized to set up an efficient virus-induced gene silencing (VIGS) system for J. regia fruit. The optimized VIGS-TRV system induced complete photobleaching phenotype on the walnut fruits of four cultivars, and the JrPDS transcript levels decreased by up to 88% at 8 days post inoculation (dpi). While those of browning-related genes JrPPO1 and JrPPO2 decreased by 67% and 80% at 8 dpi, respectively, accompanied by a significant reduction in fruit browning phenotype. Sodium dodecyl sulphate-polyacrylamide gel electrophoresis screening and Western Blot showed that the PPO protein levels were significantly reduced. Moreover, a model of TRV-mediated VIGS system for inoculating J. regia fruit with efficient silence efficiency via co-culture was constructed. These results indicate that the VIGS-TRV system established by us is an efficient tool for rapid gene function analysis in J. regia fruit.